Leadership Paradox and Efforts to Handle It in Organizational Change - Jalal, Akh; Ismail, Iriani (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This research explores the leadership paradoxes that arise when managing organizational change along with leaders' efforts in dealing with these paradoxes. This research uses a library study method, by analyzing various relevant literature sources from books, journal articles and other scientific sources. The results of this research reveal that there are four main challenges identified as paradoxes, namely resistance to change, uncertainty and complexity, risk and leader communication. In overcoming this paradox, this research shows that Kurt Lewin's model provides relevant guidance for leaders in facing the challenges of organizational change. This research provides practical and theoretical contributions to the development of effective leadership in facing the challenges of ongoing change